Karakteristik Marshall Campuran Aspal AC-WC Menggunakan filler Spent Bleaching Earth Sebagai Pengganti Abu Batu - Wawan Kurniawan; Lizar Lizar; Juli Ardita Pribadi (Jurnal Teknik Sipil Terapan, 2021)
Indonesia’s road crackdown commonly USES a flexible crackdown that a main ingredient on asphalt. One of the tools used in subthanizing aggregates with spent bleaching earth (SBE) replacing the filler SBE into teh mix of asphalt is predicted to enhance resiliencs SBE isa solid waste produced by the plants’s biofuel refinery, which included the exictence of B2 on this study aims to find out how much marshall’s characteristics affect the AC-WC asphalt replace the filler with SBE on at the first stage of testing got an optimum asphalt level next filler replacement will be done with SBE as big 0%, 25%, 50%, 75%, 100% and the result met the spesifications at SBE level 25%, with this research this waste of B2 could be used replace the filler in variations 25%